Effects of Fermentation Additives on Silage Quality, Chemical Composition, and Cyanide Residues of Ensiled Durian Peel as a Roughage Source for Ruminants - Semae, Sareena; Umar, Rusnee; Bindolah, Masitoh (Asian Health, Science and Technology Reports, 2026)
To assess durian peel as a potential ruminant feed resource, this study investigated the effects of various fermentation additives on silage quality, nutrient composition, and feed safety. The experimental design followed a completely randomized design (CRD) with three treatments: yeast, salt, and sodium nitrate. Each additive was applied at 1% of the fresh matter. The experiment was conducted in triplicate, with each replicate serving as an independent fermentation unit prepared in an individual 20-L plastic container. Fresh durian peel was manually chopped into 2–3 cm pieces, thoroughly mixed with the specified additives, and stored under anaerobic conditions for 21 days. Fermentation quality was assessed based on physical characteristics, pH, and residual hydrocyanic acid concentration. Chemical composition was analyzed using standard proximate and fiber analysis. The results showed that all treatments produced silage of acceptable quality, characterized by a favorable fermented aroma and desirable pH values. Residual hydrocyanic acid levels in across ensiled durian peel treatments remained well within safe limits for ruminant feeding. Yeast supplementation yielded the highest crude protein content and enhanced palatability, whereas salt improved physical characteristics, color stability, and gross energy. Notably, sodium nitrate was the most effective additive for reducing fiber fractions and further minimizing cyanide residues. The results indicate that durian peel can be effectively preserved and its nutritional value enhanced through ensiling with appropriate additives. Overall, yeast supplementation yielded in the highest crude protein content, while salt treatments enhanced silage physical quality and energy value. Conversely, sodium nitrate was most effective in treatment reducing fiber fractions and mitigating cyanide residues. The selection of fermentation additives should be tailored to specific production goals, such as maximizing protein content, ensuring feed safety, and optimizing cost-effectiveness. These findings suggest the potential of ensiled durian peel as a sustainable and low-cost potential roughage source for ruminants in tropical regions.